The Impact of Self-efficacy Towards Speaking Performance - I Gde Putu Agus Pramerta (Universitas Pendidikan Ganesha, 2021)
This present study is an associational study that employed simple linear regression model. There were two variables in this study such as self-efficacy as the independent variable while speaking performance as the dependent one. This study was conducted at a public university in Indonesia. The subjects recruited were 75 students. The data were collected by administering a self-efficacy questionnaire which contains 28 items. The data were analyzed quantitatively using SPSS program. The results show that mostly, the students had average and high category of SE as shown by 22.7% and 38.7% respectively. Moreover, it was found that F (1, 72) = 17.950, p < 0.001. It means that statistically there was an impact of students’ self-efficacy toward students’ speaking performance. Based on the aforementioned results, it can be concluded that the students had good potential to enhance their speaking skills and their SE had significant contribution to their speaking performance.